Energy efficiency innovations : driving prosperity, slashing emissions (World scientific series in current energy issues, 2020)
"Energy efficiency touches all parts of the economy and lies at the heart of all plausible strategies for addressing climate change. A fascinating range of new technologies and new business models have emerged in the past few years and are rapidly reshaping the field and driving efficiency improvements - many of them completely unexpected. This book provides a fresh look at energy efficiency written in a way that can be interesting to experts and serve as an entry point for novices. With chapters written by recognized experts in their fields of expertise, the book provides readers with a clear perspective on the state-of-the art developments of both new technologies and new approaches to system design and operations in buildings, industry, transportation, and urban design. Strategies for electrification and optimization based on data and powerful algorithms are also explored in depth. The discussion includes new mobility systems, smart buildings, reimagined industrial processes, new materials, and smart grid integration"--Publisher's website